2020
DOI: 10.3390/ijms21249553
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Crowding Agents on the Architectural Properties of the Bacterial Nucleoid-Associated Protein HU

Abstract: HU is a nucleoid-associated protein expressed in most eubacteria at a high amount of copies (tens of thousands). The protein is believed to bind across the genome to organize and compact the DNA. Most of the studies on HU have been carried out in a simple in vitro system, and to what extent these observations can be extrapolated to a living cell is unclear. In this study, we investigate the DNA binding properties of HU under conditions approximating physiological ones. We report that these properties are influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 47 publications
1
11
0
Order By: Relevance
“…This is in agreement with earlier observations that increasing ionic strength reduces HU binding affinity 30 . Overall our results agree with earlier observations 22 , 26 , 33 and indicate switching between two modes of binding depending on HU concentration.
Figure 3 Contour length (Lc) and persistence length (Lp) as a function of protein concentration.
…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…This is in agreement with earlier observations that increasing ionic strength reduces HU binding affinity 30 . Overall our results agree with earlier observations 22 , 26 , 33 and indicate switching between two modes of binding depending on HU concentration.
Figure 3 Contour length (Lc) and persistence length (Lp) as a function of protein concentration.
…”
Section: Resultssupporting
confidence: 93%
“…Clusters of fluorescent signals of proteins appear along the timeline in the condition without Mg 2+ and at tension above 10 pN, while no evidence for clusters is found with 8 mM Mg 2+ . In our earlier studies 33 we showed that HU dimers bind DNA with high cooperativity (both in the absence and presence of 8 mM Mg 2+ ) when there is no tension on the DNA. Similar binding behaviour of HU is expected at tension under 10 pN since the extension of the DNA is shorter than Lc below that force and thus somewhat comparable to the condition in the TPM experiment.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…The simplest models adopt single proteins, usually chosen among those known to have a low tendency to interact. Examples of these proteins are the bovine pancreatic trypsin inhibitor (BPTI), ribonuclease A, lysozyme, β-lactoglobulin, hemoglobin, and bovine serum albumin (BSA). Studies of mixed crowders were also conducted, and the advantages of mixed crowding over homogeneous crowding were independently suggested by different groups. Zhou tested, for instance, the effects of mixed crowding on protein stability and suggested that optimal crowding effects could be obtained by adjusting mixing ratios between crowders’ populations . Shah et al also suggested a role for enthalpic interactions in mixtures using an in silico approach at lower than physiological temperatures (27 °C) .…”
Section: Enthalpy Versus Entropymentioning
confidence: 99%
“…It may be useful here to distinguish between the terms 'macromolecular crowding' and 'macromolecular con nement': the dynamic effects of volume exclusion are caused in the former by other macromolecules and in the latter by the static shape and size of the system (Lecinski et al, 2021). It may also be useful to distinguish between different crowding agents, as shown for the compaction and DNA-binding of HU (Lin et al, 2020) and, in particular, to distinguish between molecular crowding and macromolecular crowding, which can affect water dynamics differently (Verma et al, 2018). Indeed, in highly crowded media, molecular crowding affects both the interstices between the crowder molecules and the interfacial water, whilst macromolecular crowding does not affect the bulk water and only has a small effect on the interfacial water (Verma et al, 2018).…”
Section: Molecular and Macromolecular Crowding Or Water Availabilitymentioning
confidence: 99%